2017
DOI: 10.1016/j.legalmed.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three-dimensional facial morphology between upright and supine positions employing three-dimensional scanner from live subjects

Abstract: Facial soft tissue thicknesses (FSTT) measurements collected from Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) imaging techniques are most commonly taken in the supine position for forensic craniofacial reconstruction. FSTT have been shown to be different in comparison to the upright position due to gravity. The variation of facial morphology between the upright and supine position of laser-scanned images taken from 44 individuals was investigated using volumetric analysis with deviation maps.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 36 publications
0
13
0
5
Order By: Relevance
“…The variation with position can be explained by many factors, among which are the gravity effect and the role of the suspensory ligaments. 23 Lifting areas highly affected by gravity need a higher tension and lifting power. This is better provided by anchoring the thread to a rigid structure like muscular fascia or bone periosteum.…”
Section: Discussionmentioning
confidence: 99%
“…The variation with position can be explained by many factors, among which are the gravity effect and the role of the suspensory ligaments. 23 Lifting areas highly affected by gravity need a higher tension and lifting power. This is better provided by anchoring the thread to a rigid structure like muscular fascia or bone periosteum.…”
Section: Discussionmentioning
confidence: 99%
“…Gravity can affect the ala nasi and nasal region if the subject undergoes CT in supine position, causing deformation of the nasal soft tissues. Bulut et al investigated how the facial soft tissue thickness is influenced by the position of the head (i.e., upright versus supine) 25 . They used 3D laser scanned facial images to compare two positions, which revealed that the largest soft tissue deviations occurred in the mouth, cheeks, and masseter region because of downward sagging of the flesh caused by gravity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous average FSTT datasets have been compiled based on living subjects using a wide range of medical imaging equipment (Drgáčová et al 2016;Parks et al 2017;Sandamini et al 2018;Ayoub et al 2019). Studies on facial soft tissue changes according to body position have also been conducted, yielding information that will be invaluable for the application of FSTT data to CFR (Baillie et al 2016;Bulut et al 2017).…”
Section: The Cfr Techniquementioning
confidence: 99%